Resistant and Susceptible Sorghum - Calbreath, Jackson; Marshall, Jeremy L.; Michaud, J.P. (My University, 2017)
In the year 2015, the USA produced 597 Million bushels of sorghum and planted 7.85 million acres. Kansas produced 281.6 million bushels and planted 3.2 million acres. With Green bug aphid and the sugarcane aphid a major pest of the sorghum crop in Kansas and sorghum being the 3rd top crop commodity in Kansas if a big infestation comes in could hurt agriculture industry as a whole. In the sorghum industry they have developed varieties that are resistance to specific types of aphids but one variety maybe resistance to one type of aphid but susceptible to another type. My project was to compare two type of aphids on 2 different varieties of sorghum and see how a resistance variety and a susceptible variety are affected by aphids. The resistance varieties will have less damage done by the aphids to the plant compared to the susceptible variety. These results are important in the state of Kansas due to Kansas being ranked 7th in the nation in agriculture production. Being an Animal Science and Industries major with the production option, milo seed is a product of sorghum, similar to corn and sometimes cheaper, we can use milo seed in feed to produce the same amount in livestock industry for less money so our production can be more profitable.